Information Bottleneck as Optimisation Method for SSVEP-Based BCI - Ingel, Anti; Vicente, Raul (Frontiers in Human Neuroscience, 2021)
In this work, the information bottleneck method is proposed as an optimisation method for steady-state visual evoked potential (SSVEP)-based brain-computer interface (BCI). The information bottleneck is an information-theoretic optimisation method for solving problems with a trade-off between preserving meaningful information and compression. Its main practical application in machine learning is in representation learning or feature extraction. In this work, we use the information bottleneck to find optimal classification rule for a BCI; this is a novel application for the information bottleneck. This approach is particularly suitable for BCIs since the information bottleneck optimises the amount of information transferred by the BCI. SSVEP-based BCIs often classify targets using very simple rules like choosing the class corresponding to the largest feature value; we call this classifier the arg max classifier. It is unlikely that this approach is optimal, and in this work, we propose a classification method specifically designed to optimise the performance measure of BCIs. This approach gives an advantage over standard machine learning methods, which aim to optimise different measures. The performance of the proposed algorithm is tested on two publicly available datasets in offline experiments. We use the standard power spectral density and canonical correlation analysis feature extraction methods on one dataset and show that the current approach outperforms most of the related work on this dataset. On the second dataset, we use task-related component analysis method and demonstrate that the proposed method outperforms the standard arg max classification rule in terms of information transfer rate when using a small number of classes. To our knowledge, this is the first time the information bottleneck is used in the context of SSVEP-based BCIs. Our approach is unique in the sense that optimisation is done over the space of classification functions. This approach potentially improves the performance of BCIs and makes it easier to calibrate the system for different subjects.